2019
DOI: 10.1097/md.0000000000016997
|View full text |Cite
|
Sign up to set email alerts
|

Association between lymphocyte subsets and cytomegalovirus infection status among patients with systemic lupus erythematosus

Abstract: This study aimed to determine the association between different lymphocyte subsets and cytomegalovirus (CMV) infection status in patients with systemic lupus erythematosus (SLE). We performed a retrospective study among SLE patients with CMV infection and collected patient socio-demographic and clinical characteristics, as well as their recorded circulating lymphocyte subsets. Univariate and multivariable logistic regression analyses examined the relationship between CMV infection status and lymphocyte subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…In one of the first studies determining the characteristics of COVID‐19 infection Guan et al showed that Lymphopenia was observed in 82.1% of patients 11 . In several studies it has been found that the lymphocyte percentage descend with the disease, which indicates the direct result of viral infection 12‐14 . And last component of this novel scoring model is the absence of a respiratory symptom dyspnoea; in a meta‐analysis by Hu et al showed that the incidence of dyspnoea was 21.4% (95CI 15.3%‐27.5%) in COVID‐19 infected patients 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of the first studies determining the characteristics of COVID‐19 infection Guan et al showed that Lymphopenia was observed in 82.1% of patients 11 . In several studies it has been found that the lymphocyte percentage descend with the disease, which indicates the direct result of viral infection 12‐14 . And last component of this novel scoring model is the absence of a respiratory symptom dyspnoea; in a meta‐analysis by Hu et al showed that the incidence of dyspnoea was 21.4% (95CI 15.3%‐27.5%) in COVID‐19 infected patients 15 .…”
Section: Discussionmentioning
confidence: 99%
“…24,34,35 Cytomegalovirus D 1 1 2 X Xand upper respiratory tract viral infections are common in the SLE population, and may present with severe and atypical manifestations that mimic SLE flares. 28,36 Respiratory infections are one of the most common causes of hospitalization and early mortality in patients with SLE. 22 Elderly individuals (65 years of age) with rheumatic conditions are at greater risk of influenza and influenza-related complications.…”
Section: Relationship Between Sle and Risk Of Viral Infectionsmentioning
confidence: 99%
“… 24 , 34 , 35 Cytomegalovirus (CMV) and upper respiratory tract viral infections are common in the SLE population, and may present with severe and atypical manifestations that mimic SLE flares. 28 , 36 …”
Section: Relationship Between Sle and Risk Of Viral Infectionsmentioning
confidence: 99%
“…HCMV infection is also known to trigger SLE flares through direct cytopathic effects and/or activation of inflammatory processes, thus causing both systemic and organ-specific disease. Lastly, the clinical features of HCMV infection themselves happen to mimic SLE flares, further complicating the clinical picture of SLE patients [ 134 ].…”
Section: The Main Autoimmune Diseases Associated With Hcmv Infectimentioning
confidence: 99%